Acute Flare of Bullous Pemphigus With Pembrolizumab Used for Treatment of Metastatic Urothelial Cancer. Issue 1 (January 2018) - Garje, Rohan; Chau, Justin J.; Chung, Jina; Wanat, Karolyn; Zakharia, Yousef
Abstract : In the past decade, the resurgence of immunotherapy has changed the landscape of cancer therapy. Checkpoint inhibitors targeting cytotoxic T-lymphocyte antigen-4, programmed death-1 on lymphocytes, and programmed death ligand-1 on tumors cells are currently utilized in the management of several cancers. These agents are double-edged sword with the positive effect being robust antitumor response but on the other side they can throttle up the normal immunologic homeostasis in a negative way, leading to adverse autoimmune toxicities. These adverse toxicities are frequent if patients have active autoimmune disorders. Here, we report a rare case of quiescent bullous pemphigoid which flared after initiation of pembrolizumab, a programmed death ligand-1 inhibitor.